Analysis of the Impact of Supply Chain Relationship Strategy on Corporate Cash Dividend Policy Based on Chinese Data - Yang, Xingquan; Sun, Lingyan (Frontiers in Public Health, 2022)
With the development and application of e-commerce in the process of supply chain integration, the choice of supplier centralized strategy or decentralized mode and how to use supplier financing have become significant contents of supply chain management. This paper investigates the effect of competition and cooperation on the corporate cash dividend policy under the influence of the supplier relationship strategy and its mediating mechanism based on big data. The motivation of this paper is to provide a basis for enterprises to grasp the dynamic evolution process of the economic consequences of supply chain relationship based on big data and adjust the relationship strategy in time to maximize the positive effects of supplier relationship. This paper considers supplier concentration and supplier financing as two dimensions to measure the supplier relationship strategy and selects the balanced panel data of Chinese A-share listed companies from 2007 to 2020 as samples by applying the Logit and Tobit model. The results demonstrate that the supplier relation is negatively correlated with the cash dividends. The intermediary effect found that the competition effect of the supplier relationship aggravates the agency conflict of enterprises and intensifies the degree of financing constraints, and thus acts on the cash dividends of enterprises. This paper expands the economic consequences of relational transactions and provides the explanation of dividend policies from the perspective of a supply chain.